2020
DOI: 10.1507/endocrj.ej19-0205
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among body composition and metabolic regulation in a male mouse model of Cushing’s syndrome

Abstract: Glucocorticoids play a critical role in the regulation of homeostasis, including metabolism. In patients with Cushing's syndrome, chronic glucocorticoid excess disrupts physiological internal milieu, resulting in central obesity, muscle atrophy, fatty liver, and insulin resistance. However, the relationship among various metabolic effects of glucocorticoids remains unknown. In the present study, we studied a male mouse model of Cushing ' s syndrome and indicated that glucocorticoid excess alters metabolic phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Male mice were exposed to oral treatments (n = 10/treatment) at target doses consisting either of corticosterone (100 µg/ml at the beginning of the treatment and lowered to 50 µg/ml on day 20 of the study), mirabegron (0.0048 or 0.048 mg/ml), vehicle (<1% ethanol), or naïve control (autoclaved water). The dose of 100 µg/ml of oral corticosterone was selected as it was the dose that has been found to model Cushing's disease, metabolic syndrome, and stress‐related obesity (Fransson et al, 2013 ; Karatsoreos et al, 2010 ; Tamashiro et al, 2011 ; Uehara et al, 2020 ). Mirabegron, a β3AR agonist known to increase BAT activity, was used as a positive control in order to compare the effects of corticosterone against changes observed in BAT under chronic activation.…”
Section: Methodsmentioning
confidence: 99%
“…Male mice were exposed to oral treatments (n = 10/treatment) at target doses consisting either of corticosterone (100 µg/ml at the beginning of the treatment and lowered to 50 µg/ml on day 20 of the study), mirabegron (0.0048 or 0.048 mg/ml), vehicle (<1% ethanol), or naïve control (autoclaved water). The dose of 100 µg/ml of oral corticosterone was selected as it was the dose that has been found to model Cushing's disease, metabolic syndrome, and stress‐related obesity (Fransson et al, 2013 ; Karatsoreos et al, 2010 ; Tamashiro et al, 2011 ; Uehara et al, 2020 ). Mirabegron, a β3AR agonist known to increase BAT activity, was used as a positive control in order to compare the effects of corticosterone against changes observed in BAT under chronic activation.…”
Section: Methodsmentioning
confidence: 99%
“…Dexamethasone, a potent synthetic glucocorticoid, is known to lead to changes in the metabolisms of carbohydrates, lipids, and proteins and to act in other tissues, in a time and dose-dependent manner [3]. Additionally, chronic glucocorticoid excess disrupts the internal milieu, resulting in central obesity, muscle atrophy, and fatty liver [21]. Given the severity of this disease, we sought to standardize a rat model of Cushing's syndrome induced by chronic glucocorticoid over levels and then to assess the potential effects of the administration of the branched-chain amino acid leucine on the pathophysiological process since there are few studies regarding the systemic effects of this amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…Male adult Wistar rats (Rattus norvegicus) weighing between 250-300 g were obtained from the Biotherium of the Center of Agricultural Sciences of Federal University of Piauí. The animals were kept under controlled conditions of temperature (22 ± 2ºC), relative humidity of 55 ± 10% and a light-dark cycle (lights on from 6 a.m. to 6 p.m.), with free access to water and food (Presence®, Paulínea, SP, Brazil), following the guidelines for the ethical use of animals (21), which was previously approved by the Animal Ethics and Experimentation Committee of the Federal University of Piauí (protocol number 314/17).…”
Section: Animals and Proceduresmentioning
confidence: 99%
“…Protein breakdown and lipid metabolism in skeletal muscle are essential for maintaining normal bone cell function [41]. With changes in diet, bone cells can adversely affect the skeletal system by altering the activity of glucocorticoid levels causing muscle wasting, osteoporosis, and insulin resistance [42]. A large number of studies have shown that secondary osteoporosis, muscle atrophy, insulin resistance, and type 2 diabetes caused by excessive glucocorticoid in skeletal muscle are mainly caused by high-fat diets [43].…”
Section: Discussionmentioning
confidence: 99%